The study on the influence factors toward employee performance in University Tun Hussein Onn Malaysia (UTHM) / Masturah Azman and Izyan Diyana Hamdan - Azman, Masturah; Hamdan, Izyan Diyana (2016)
This study seeks to investigated the factors influence employee performance among the staffs at University Tun Hussein Onn Malaysia (UTHM). The objective of this study were to examine the factors that influence employee performance among the staffs. Besides that, it also implement to know the relationship between physical component of environment, interaction and learning commitment with employee performance. The literature state that the workplace environment plays a crucial role for employee (Demet, 2012). Nowadays, there are various type of working environment can be choose by employee, so that it become on of the crucial factors for keeping or accepting the jobs. Interaction and distraction such as social interaction, work interaction, creative physical environment, overall atmosphere, position relative to colleagues, position relative to equipment, overall office layout and refreshments. It is evident in the research findings of Patterson et al.,(2003) that the more satisfied workers are with their jobs the better the company is likely to perform in terms of subsequent profitability and particularly productivity. Learning commitment (organizational commitment) has been one of the most exciting topics researchers since the 1960s. Many studies have been conducted on loyalty and its impact on employees’ work attitudes and behaviors (Sulaiman & Al-Junaibi, Commitment and turnover intention in the UAE oil industry, 2010). The performance of any organization depends heavily on its employee’s commitment. Therefore, organizational commitment is considered as a key factor that determines organizations’ success (Mohsan, 2011). This paper presents the analysis of the most influence factors that effect on employee performance and examine the relationship between physical component of environment, interaction and learning commitment towards employee performance.